Effects of Nonpeptide and Selective V1 and V2 Antagonists on Blood Pressure Short-Term Variability in Spontaneously Hypertensive Rats - Nina Japundžic-Žigon; Sanja Milutinović; Aleksandar Jovanović (Elsevier, 2004)
Effects of V1 (OPC-21268) and V2 (OPC-31260) vasopressin antagonists on blood pressure (BP) short-term variability were investigated in adult spontaneously hypertensive rats (SHR) under basal conditions and after the stimulation of vasopressin release by hemorrhage. BP was recorded intra-arterially and sampled at 20 Hz to be analyzed on a personal computer. BP time spectra were calculated on 30 stationary overlapping 2048 point-time series. Spectral power was estimated in total (0.00976 - 3 Hz), very low frequency (VLF: 0.00976 - 0.195 Hz), low frequency (LF: 0.195 - 0.605 Hz), and high frequency (HF: 0.8 - 3 Hz) regions. Under basal conditions a V1 antagonist (5 mg/kg, i.v.) decreased BP without affecting BP variability, while combined (V1 +V2) blockade or V2 blockade (1 mg/kg, i.v.) alone did not affect cardiovascular parameters. Mild hemorrhage (5 ml/kg per min) increased HF-BP variability, while moderate (10 ml/kg per min) and massive (15 ml/kg per min) hemorrhage did not affect it. In V1, but not V2, antagonist pre-treated SHR HF-BP increased significantly after moderate and massive hemorrhage. V1 or V2 antagonist pre-treatment also enhanced VLF-BP variability during massive hemorrhage. Moreover V1 blockade prevented hemorrhage-induced bradycardia, while V2 blockade potentiated it. It follows that in adult SHR, vasopressin buffers BP oscillations in HF and VLF frequency domains only in hypovolaemic conditions and that the modulation of the autonomic adjustment of the HR to hemorrhage by vasopressin is preserved. Keywords:: blood pressure variability, spectral analysis, vasopressin antagonist, hemorrhage, hypertension